Under New Ownership : Privatizing China's State-Owned Enterprises - Yusuf, Shahid (Washington, DC: World Bank and Stanford University Press, 2012)
This publication is organized as follows: Chapter 1, discuses China's industrial system: where it is now, where it should be headed, and why. Chapter 2, contains reform in China. Chapter 3, discusses the accelerated change in enterprise ownership 1997-2003. Chapter 4, covers Chinese ownership reform in the East European mirror. Chapter 5, discusses assessing the effects of ownership reform in China. Chapter 6, considers making privatization work.